Tradition of Makan Sempulung and Its Preservation in Wajok Mempawah West Kalimantan - hairani, mita (The Pontianak State Institute of Islamic Studies, 2018)
This article is the result of research that discusses local culture and its interactions with Islam. Researchers want to show how Islam interacts with local culture and accepts it as part of the Islamization process. The data used here is obtained through interviews with elders and community figures, and based on their own experiences living in the middle of Bugis community. Based on the results of data collection in the field, it was obtained an illustration that this tradition was considered by some people to be an old tradition of shirk, so they left it. However, some people see that this heritage culture is quite important and positive for their lifes. As a heritage culture, they feel they have the duty to maintain it and continue to carry it out